THE EXISTENCE OF SUSTAINABLE SETTLEMENT IN SURABAYA AS AN ATTEMPT TO REALIZE ECO CITY - Nadhila Retnasari Roestam; Ayu Sri Marita; Nadia Maulina Atrisandi; Purwanita Setijanti (Journal of Architecture&ENVIRONMENT, 2013)
The existence of kampungs or township settlements in Surabaya is very essential to the city development seen from the historical aspect of Surabaya which grew from the development of township settlements. Therefore the issue of sustainable develop-ment to create a good living environment can be applied to the settlements sector in Surabaya in order to turn Surabaya into an ecological city, so that the efforts of citi-zens in Surabaya in the eco kampung activities can make a significant contribution in the realization of the ecological city. Kampung Kertajaya Surabaya is one of the township settlements in Surabaya that applies sustainable development with the coo-peration of the residents and City Government.